Ginsenoside compound K reduces neuronal damage and improves neuronal synaptic dysfunction by targeting Aβ - Li, Na; Pang, Qihang; Zhang, Yanhong; Lin, Jianan; Li, Hui; Li, Zhen; Liu, Yaxin; Fang, Xingyu; An, Yu; Bai, Haonan; Li, Dianyu; Cao, Zhanhong; et al. (Frontiers in Pharmacology, 2023)
Background: Alzheimer’s disease (AD) is the most common neurodegenerative condition worldwide, with amyloid β (Aβ) fibrils presenting as its main pathological feature. This study investigated whether Ginsenoside Compound K (CK) has activity against Aβ and its mechanism in reducing synaptic damage and cognitive impairment. Methods: The binding capacity of CK to Aβ42 and Nrf2/Keap1 was determined using molecular docking. Transmission electron microscopy was used to monitor CK-mediated degradation of Aβ fibrils. The effect of CK on the survival of Aβ42-damaged HT22 cells was determined using a CCK-8 assay. The therapeutic efficacy of CK in a scopoletin hydrobromide (SCOP) induced cognitive dysfunction mouse model was measured using a step-down passive avoidance test. GO enrichment analysis of mouse brain tissue was peformed using Genechip. Hydroxyl radical scavenging and reactive oxygen species assays were performed to verify the antioxidant activity of CK. The effects of CK on the expression of Aβ42, the Nrf2/Keap1 signaling pathway, and other proteins were determined by western blotting, immunofluorescence, and immunohistochemistry. Results: Molecular docking results showed that CK interacts with Lys16 and Glu3 of Aβ42. CK reduced the aggregation of Aβ42 as observed using transmission electron microscopy. CK increased the level of insulin-degrading enzyme and decreased the levels β-secretase and γ-secretase; therefore, it can potentially inhibit the accumulation of Aβ in neuronal extracellular space in vivo. CK improved cognitive impairment and increased postsynaptic density protein 95 and synaptophysin expression levels in mice with SCOP-induced cognitive dysfunction. Further, CK inhibited the expression of cytochrome C, caspase-3, and cleaved caspase-3. Based on Genechip data, CK was found to regulate molecular functions such as oxygen binding, peroxidase activity, hemoglobin binding, and oxidoreductase activity, thus affecting the production of oxidative free radicals in neurons. Further, CK regulated the expression of the Nrf2/Keap1 signaling pathway through its interaction with the Nrf2/Keap1 complex. Conclusion: Our findings show that CK regulates the balance between Aβ monomers production and clearance, CK binds to Aβ monomer to inhibits the accumulation of Aβ, increases the level of Nrf2 in neuronal nuclei, reduces oxidative damage of neurons, improves synaptic function, thus ultimately protecting neurons.